2021
DOI: 10.1021/acs.jced.0c00742
|View full text |Cite
|
Sign up to set email alerts
|

Ideal-Gas Thermochemical Properties for Alkanolamine and Related Species Involved in Carbon-Capture Applications

Abstract: Ideal-gas thermochemical properties (enthalpy, entropy, Gibbs energy, and heat capacity, C p) of 49 alkanolamines potentially suitable for CO 2 capture applications and their carbamate and protonated forms were calculated using two high-order electronic structure methods, G4 and G3B3 (or G3//B3LYP). We also calculate for comparison results from the commonly used B3LYP/aug-cc-pVTZ method. This data is useful for the construction of molecular-based thermodynamic models of CO 2 capture processes involving these s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We have previously shown that the uncertainty in the IG reaction enthalpies is very similar to that of the IG reaction free energies, for which we used the standard deviation of the IG results from G4, G3, CBS-QB2, and CBS-APNO calculations as a surrogate uncertainty measure. The data in Table indicate that the IG contribution to the uncertainty in the deprotonation reaction enthalpies at 298.15 K is smaller than 0.5 p K a units (≈2.85 kJ) in all cases.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the uncertainty in the IG reaction enthalpies is very similar to that of the IG reaction free energies, for which we used the standard deviation of the IG results from G4, G3, CBS-QB2, and CBS-APNO calculations as a surrogate uncertainty measure. The data in Table indicate that the IG contribution to the uncertainty in the deprotonation reaction enthalpies at 298.15 K is smaller than 0.5 p K a units (≈2.85 kJ) in all cases.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The 10 lowest-energy conformers of each solute at the MMFF94 level were further optimized using the Gaussian 16 package, followed by frequency calculations using high-level composite methods (G4, G3, CBS-QB3, and CBS-APNO) to find the lowest-free-energy conformer for each QM method at 298.15 K. For a given QM method, the free energies of the most stable conformers were then used to calculate the IG reaction free energies at T = 298.15 K; to save computational time, the effect of temperature on the reaction free energy was implemented only using G4 calculations over the temperature range of 283.15–373.15 K according to where Δ G j 0 (298.15; P 0 ) avg is the average value of the reaction free energy using G4, G3, CBS-QB3, and CBS-APNO calculations and [Δ G j 0 ( T ; P 0 ) – Δ G j 0 (298.15; P 0 )] G4 is that of G4 calculations. We have previously shown that the second term, which accounts for the effect of temperature on the IG free energy, is insensitive to the QM method/theory level; however, the absolute IG free energy of the species (the first term) can vary substantially across different QM methods. As noted previously, improved predictions can arise from the use of the combination of several high-level QM methods for the calculation of this term.…”
Section: Computational Detailsmentioning
confidence: 99%